Tinjauan Pustaka : Keratokonus - Ardian Reza Putra; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
sexes and all ethnicities. The estimated prevalence in the general population is 54 per 100,000. Ocular signs and symptoms vary depending on the severity of the disease. The initial shape is usually unknown unless closure topography is performed. Disease progression is manifested by a loss of visual acuity that cannot be compensated for by spectacles. Edge thinning often sucks ectasia. In moderate and more severe cases, a hemosiderin arc or circular line, known as a Fleischer ring, is often seen around the base of the needle. Vogt's striae, which are fine vertical lines produced by compression of Descemet's membrane, are another characteristic. Most patients eventually develop scar tissue. Munson's sign, V-shaped deformation of the lower eyelid in the downward position; Rizzuti's sign, bright reflection of the nasal limbal region when light is directed to the temporal limbal region; and damage to Descemet's membrane leading to acute stromal edema, known as hydrops, is observed in advanced stages. . Genetic, biomechanical, and biochemical theories about the causes of keratoconus have been put forward. Treatment varies depending on the severity of the disease. This article provides a review of the definition, epidemiology, etiology, pathogenesis, clinical features, diagnosis of keratoconus.